Site-specific modification and RNA crosslinking of the RNA-binding domain of PKR - Spanggord, Richard J. (Oxford University Press, 2000)
RNA-dependent protein kinase (PKR) is an interferon-induced, RNA-activated enzyme that phosphorylates and inhibits the function of the translation initiation factor eIF-2. PKR is activated in vitro by binding RNA molecules with extensive duplex structure. To further define the nature of the RNA regulation of PKR, we have prepared and characterized site-specifically modified proteins consisting of the PKR 20 kDa RNA-binding domain (RBD). Here we show that the two cysteines found naturally in this domain can be altered by site-directed mutagenesis without loss of RNA binding affinity or the RNA-regulated kinase activity. Introduction of cysteine residues at other sites in the PKR RBD allows for site-specific modification with thiol-selective reagents. PKR RBD mutants reacted selectively with a maleimide to introduce a photoactivatable crosslinking aryl azide at three different positions in the protein. RNA crosslinking efficiency was found to be dependent on the amino acid modified, suggesting differences in access to the RNA from these positions in the protein. One of the amino acid modifications that led to crosslinking of the RNA is located at a residue known to be an autophosphorylation site, suggesting that autophosphorylation at this site could influence the RNA binding properties of PKR. The PKR RBD conjugates described here and other similar reagents prepared via these methods are applicable to future studies of PKR–RNA complexes using techniques such as photocrosslinking, fluorescence resonance energy transfer and affinity cleaving.